Genetic relationship between bacterial wilt resistance and yield components in peanut - Jianbin Guo; Nian Liu; Huaiyong Luo; Li Huang; Xiaojing Zhou; Weigang Chen; Bolun Yu; Huifang Jiang; Yong Lei; Boshou Liao (Oil Crop Science)
Bacterial wilt (BW) caused by Ralstonia solanacearum is a wide-spread and serious disease in peanut. To date, this soilborne disease could only be effectively controlled by planting resistant peanut cultivars. However, the relatively lower yield potential of the available BW-resistant peanut cultivars is a key reason restricting productivity in most epidemic regions naturally infested with the pathogen. Even small pods or seeds and low number per plant has been regarded as the key factor for the low yield potential both in BW-resistant peanut germplasm lines and available released cultivars, whether the resistance is closely linked with key yield components remains unclear. In this study, the relationship between pod weight and BW resistance was analyzed by using a recombinant inbred lines (RIL) population derived from a crossing combination between a high yielding cultivar Xuhua 13 and a BW-resistant cultivar Zhonghua 6. From the experiments, it was found that the BW resistance was not significantly correlated with pod number per plant (PNP), hundred pod weight (HPW) and pod weight per plant (PWP) in the RIL population. Based on linkage analysis, the quantitative trait locus (QTL)s related to PNP were identified on A06, A07, A08 and B03. The QTLs for HPW were detected on A05 and A07, and the QTLs for PWP were on A06, A07 and B03. However, the QTL for BW resistance identified on B02. These results indicated that the BW resistance and the pod number per plant as well as pod weight were inherited independently. Two recombined lines (QT0944 and QT1028) with high level BW resistance and large pods (hundred pod weight over 185g) were identified from the RILs, and they possessed the favored alleles of identified QTLs from both parents, which could be used in peanut breeding for high yield and high level disease resistance.